Dansyl linked solid phase resins as an educational tool to teach the concepts of high throughput screening and prodrugs. - Jordi Morral; Ali Ibrahim; Fatima Traore; Klaus Pors (University of Huddersfield Press, 2023)
High throughput screening (HTS) and combinatorial chemistry, have been part of the process of drug design for nearly two decades. However, methods to teach their practical aspects to undergraduate students are scarce in the literature. The authors describe the synthesis and reactivity, under hydrolytic and transesterification conditions, of newly prepared fluorescent solid phase resins, envisaged to teach the concept of HTS, and prodrugs, to undergraduate students. Although the enzymatic methods did not perform well, the chemical hydrolysis, and the transesterification reaction, of these new solid phase resins, worked in very good yields, and produced very useful results. In relation to the experiment, the student's learning experience, and feedback, were very positive.